Influence of WC-Co hard metal microstructure on defect density, initiation and propagation kinetics of fatigue cracks starting at intrinsic and artificial defects under a negative stress ratio. (15th April 2020) - Klünsner, T.; Lube, T.; Gettinger, C.; Walch, L.; Pippan, R.
Abstract: The fracture behavior of WC-Co hard metals depends on the size of material inhomogeneities or defects from which cracks emanate. The size and frequency of these defects is of high significance to the quantitative understanding of the failure behavior of structural components and metalworking tools made of hard metal. Currently, the interdependence of a hard metal's microstructure, its defect density, its crack nucleation and growth kinetics and its observed fatigue behavior is not completely understood. The current work provides information on the defect density, fatigue limits, fatigue crack initiation thresholds and growth kinetics at a cyclic mean stress of zero for various hard metal grades as a function of their microstructure. The average WC grain size of the investigated materials varied from ultrafine to medium; the Co binder content ranged from 9 to 15 wt.%. The distribution of size and density of defects was determined by analytic relations based on Weibull theory applied to strength distributions determined in three-point bending experiments performed under monotonously increasing load. Fatigue limits were derived from stress amplitude-life curves determined in a six-point bending arrangement under a stress ratio R = σ min / σ max = –1. Crack growth kinetics were determined for the same stress ratio for artificially cracks in eight-point bending, as well as for cracks emanating from intrinsic subsurface material defects in six-point bending. The observed differences in the fatigue behavior are discussed based on the determined defect densities and the influence of ambient air / vacuum conditions on crack initiation and growth. Graphical abstract: Image, graphical abstract